Judicial Considerations of the Kota Bharu High Court of Malaysia in Acquitting an Indonesian Migrant Worker’s Death Penalty - Wafda vivid izziyana; Sukimin; Endah Puji Astuti; Eva Dwi (Jurnal Jurisprudence, 2024)
ABSTRACT Purpose of the study: This paper aims to provide an in-depth analysis of the judges' considerations in case number HC-42KB-7-04/2014 at the High Court of Kota Bharu, Malaysia. This paper specifically aims to explore the philosophical, historical, psychological, and sociological aspects that influenced the decision to release an Indonesian migrant worker from a death penalty charge. The considerations of Malaysian judges were guided by the applicable law, facts of the case, principles of justice, legal precedents; social considerations and due process of law. Methodology: This was socio-legal research with a comparative legal approach that examined how the law functions and is applied in society, taking into account the social, cultural and economic contexts that influence it. Results: The analysis of the judges' reasoning in Wilfrida Soik's case (HC-42KB-7-04/2014) by the Kota Bharu High Court highlights the importance of a holistic approach to law enforcement. The court emphasized substantive justice by integrating written law with the human condition, particularly the mental state of the accused. This decision reflects the influence of the diplomatic relations between Indonesia and Malaysia, respect for sovereignty, and international conventions. Psychologically, the defendant's mental state was disturbed, showcasing the justice system's attention to individual well-being. Sociologically, the judgment underscored the interplay of social and cultural factors, promoting rehabilitation alongside punishment. This multidimensional approach reinforces fairness and social justice in legal decisions. Applications of this study: The results of this research may inspire judicial institutions to make decisions based on considerations of inconsistency of evidence; lack of murderous intent; humanitarian consideration; criminal policy; and parole consideration. This is because many factors must be considered when making a decision, especially in the case of a death row. Novelty/Originality of this study: The analysis of Wilfrida Soik's case underscores a holistic approach to law enforcement, emphasizing substantive justice, mental health, and sociocultural factors. This novel research reveals how these considerations led to the decision to spare the accused from the death penalty, highlighting fairness and social justice. Keywords: Judicial considerations, Indonesian migrant workers, death penalty.   ABSTRAK  Tujuan penelitian: Makalah ini bertujuan untuk memberikan analisis mendalam tentang pertimbangan hakim dalam perkara nomor HC-42KB-7-04/2014 di Pengadilan Tinggi Kota Bharu, Malaysia. Makalah ini secara khusus bertujuan untuk mengeksplorasi aspek filosofis, historis, psikologis, dan sosiologis yang memengaruhi keputusan untuk membebaskan seorang pekerja migran Indonesia dari dakwaan hukuman mati. Pertimbangan hakim Malaysia dipandu oleh hukum yang berlaku, fakta-fakta kasus, prinsip-prinsip keadilan, preseden hukum; pertimbangan sosial dan proses hukum yang wajar. Metodologi: Penelitian ini merupakan penelitian sosio-hukum dengan pendekatan hukum komparatif yang mengkaji bagaimana hukum berfungsi dan diterapkan dalam masyarakat, dengan mempertimbangkan konteks sosial, budaya, dan ekonomi yang memengaruhinya. Hasil: Analisis penalaran hakim dalam perkara Wilfrida Soik (HC-42KB-7-04/2014) oleh Pengadilan Tinggi Kota Bharu menyoroti pentingnya pendekatan holistik terhadap penegakan hukum. Pengadilan menekankan keadilan substantif dengan memadukan hukum tertulis dengan kondisi manusia, khususnya kondisi mental terdakwa. Putusan ini mencerminkan pengaruh hubungan diplomatik antara Indonesia dan Malaysia, penghormatan terhadap kedaulatan, dan konvensi internasional. Secara psikologis, kondisi mental terdakwa terganggu, yang menunjukkan perhatian sistem peradilan terhadap kesejahteraan individu. Secara sosiologis, putusan tersebut menggarisbawahi interaksi faktor sosial dan budaya, yang mendorong rehabilitasi di samping hukuman. Pendekatan multidimensi ini memperkuat keadilan dan keadilan sosial dalam keputusan hukum.   Aplikasi penelitian ini: Hasil penelitian ini dapat menginspirasi lembaga peradilan untuk membuat keputusan berdasarkan pertimbangan ketidakkonsistenan bukti; kurangnya niat membunuh; pertimbangan kemanusiaan; kebijakan kriminal; dan pertimbangan pembebasan bersyarat. Hal ini karena banyak faktor yang harus dipertimbangkan saat membuat keputusan, terutama dalam kasus hukuman mati.   Kebaruan/Keaslian penelitian ini: Analisis kasus Wilfrida Soik menggarisbawahi pendekatan holistik terhadap penegakan hukum, yang menekankan keadilan substantif, kesehatan mental, dan faktor sosial budaya. Penelitian baru ini mengungkap bagaimana pertimbangan-pertimbangan tersebut berujung pada keputusan untuk membebaskan terdakwa dari hukuman mati, dengan menonjolkan keadilan dan keadilan sosial.  Kata kunci: Pertimbangan hukum, pekerja migran Indonesia, hukuman mati.